Detection and partial molecular characterization of Grapevine fleck virus, Grapevine virus D, Grapevine leafroll-associated virus -5 and -6 infecting grapevines in Brazil - Fajardo,Thor Vinícius Martins (2012)
Grapevine fleck, rugose wood and leafroll are three grapevine viral diseases whose causal agents (or associated viruses) respectively are Grapevine fleck virus (GFkV), Grapevine virus D (GVD) and Grapevine leafroll-associated virus 5 and 6 (GLRaV-5 and -6). The objective of this work was to perform a partial molecular characterization of local isolates of these four viral species that infect grapevines. The nucleotide and deduced amino acid sequences of complete genes of the coat protein (CP) (of GFkV), the CP and the RNA binding protein (of GVD), the CP and the partial hHSP70 gene (of GLRaV-5) and the partial hHSP70 gene (of GLRaV-6) were aligned and compared in silico with other isolates. These data extend the available information about Brazilian isolates of GFkV, GLRaV-5 and -6, and reports for the first time the GVD occurrence in Brazil.